Resilience of ethical and nonethical stock during COVID-19 crisis: a case of Indonesia stock exchange - Qoyum, Abdul; AlHashfi, Rizqi Umar; Hanafi, Mamduh Mahmadah; Mohd Thas Thaker, Hassanudin; Effendi, Jaenal (Emerald Publishing, 2026)
Purpose This study aims to empirically investigates the effect of the COVID-19 pandemic on ethical and nonethical stocks in Indonesia. Ethical stocks which are characterized by moral-based companies’ activities and lower debt are expected to have better resilience during the COVID-19 crisis compared to nonethical stock. Design/methodology/approach This study observes 589 firms of ethical and nonethical stock during sample periods ranging from March 2, 2020 (first case announced) to June 30, 2021. Panel regression, with some control variables, was applied. Findings Testing firms in Indonesia revealed a significant difference in stock resilience, in which ethical stock has a better resilience compared to nonethical, with Islamic socially responsible investment (SRI) stock having the highest resilience, followed by Islamic stock and then SRI stock. This study documents a significant effect of some financial criteria on the stock resilience, namely, return market (RM), market capitalization (MCAP) and share turnover (TURN). Overall, after splitting the sample into different time horizons, this study consistently reveals that ethical firms have better resilience compared to nonethical stocks. Research limitations/implications This study makes several contributions to the literature on Islamic finance, especially concerning Islamic screening with SRI factors. In practical terms, this study supports the argument that focusing on integrating environmental, social and governance criteria in sharia screening will improve the quality of Islamic firms. The “Islamic” label is not only a marketing label but also a quality certification. Originality/value This study can be used as a reference for developing Islamic finance more focused on sustainability issues including socioeconomic and human development by improving the quality of screening of Islamic firms. Therefore, this study suggests that the establishment of Islamic SRI index is very crucial and significant to promote ethical-based investment